Porous Pr(III)-based organic framework for dye-adsorption and photo degradation with (4, 5)-c net. (1st October 2019) - Du, Xieao; He, Haiyan; Du, Liting; Li, Weiqi; Wang, Yibin; Jiang, Quanguo; Yang, Lu; Zhang, Jianfeng; Guo, Shengping
Graphical abstract: A novel lanthanide–organic framework [Pr(TBDC)1.5 (H2 O)]·8H2 O·3.5DMF, (HU11, H2 TBDC = 2, 3, 5, 6-tetramethyl-1, 4-benzenedicarboxylic acid), has been isolated through hydrothermal reaction. The 3D porous architecture with (4, 5)-c net can adsorp Congo red over 95% after 24 h. As a photocatalyst, HU11 degrades the dye totally in one day with a similar band gap (3.3 eV) as TiO2 . Abstract: A novel lanthanide–organic framework [Pr(TBDC)1.5 (H2 O)]·8H2 O·3.5DMF, (HU11, H2 TBDC = 2, 3, 5, 6-tetramethyl-1, 4-benzenedicarboxylic acid), has been isolated through solvothermal reaction. Single-crystal X-ray diffraction reveals the compound features a 3D porous architecture with (4, 5)-c net. A fast adsorption rate of Congo red withHU11 was observed in the dark, but under irritation the degradation rate of the dye was visibly increased. Through UV diffuse reflection spectrum, the band gap ofHU11 with 3.3 eV has been detected, which is similar as the tradition photocatalyst TiO2 .